Peranan Pemeriksaan Multidetector Computed Tomography (Mdct) Abdomen Pada Pasien Pra Operasi Donor Ginjal - Chairunnissa, Frida Risviani; Dartini, Dartini; Mulyati, Sri (CV. Ulil Albab Corp, 2025)
Kidney transplant is the best treatment method for the patient with end stage renal disease. The final step of evaluation in living kidney donors need MDCT abdomen procedure. The aim of this study to assess the role of MDCT abdomen in pre operation living kidney donors and to assess the role of processing image in MDCT abdomen examination pre operation living kidney donors. The type of this research is descriptive research with literature review approach. This research showed that the role of MDCT abdominal examination in preoperative patients in living kidney donor is can explain anatomy, pathology, and anomalies of the arteries and veins, kidneys, ureters, using pre-contrast phase, arterial phase, nephrogram phase, and delayed phase. Obtain information from MDCT abdomen examination is used for preparation and management of surgery in order to reduce the risk of complicationts for the donor and recipient. The role of image reconstruction in MDCT abdomen examinations is useful in providing quality image regarding the anatomy of blood vessel. Image reconstruction of 3D MIP and VRT is very helpful in evaluating artery and vein of the kidney vessels.